Metal free triad from red phosphorous, reduced graphene oxide and graphitic carbon nitride (red P-rGO-g-C3N4) as robust electro-catalysts for hydrogen evolution reaction - Jaiswal A.; Pal S.; Kumar A.; Prakash R. (My University, 2025)
We have developed a robust non-metal based electrocatalyst in which different weight amounts of red phosphorus (P) are embedded into binary rGO-g-C3N4 by hydrothermal treatment. Catalyst is prepared in a cost effective single step hydrothermally without any pre-treatment of graphitic carbon nitride (g-C3N4) and structural analysis has performed through XRD (X-ray diffraction), FT-IR (Fourier Transform Infra-Red) spectroscopy and XPS (X-ray Photoelectron Spectroscopy). FE-SEM (Field Emission-Scanning Electron Microscopy) and TEM (Transmission Electron Microscopy) images show porous intimate structure of binary rGO-g-C3N4 along with red P. In addition, BET (Brunauer-Emmett-Teller) measurement confirms the mesoporous nature of the prepared composites owing to hydrothermal treatment. Catalyst with an optimum combination of red P (30% wt.), reduced graphene oxide (rGO; fix weight of 5% in all composites) and g-C3N4 demonstrates its excellencies in the hydrogen evolution reaction (HER) of water in acidic medium with lowest onset over potential of −146 mV and Tafel slope of 122.5 mV dec−1 among its counterparts. The current stability performance is also quite stable around 72 mA cm−2 and performance increases with time owing to enhancement in porosity of the composite. A detailed mechanism for enhancement into electrocatalytic property of ternary red P-rGO-g-C3N4composite has been discussed. This work will lead to exploration of more avenues for designing and framing non-metal based electrocatalyst for hydrogen evolution. © 2020 Elsevier Ltd